An integrated biological-electrocatalytic process for highly-efficient treatment of coking wastewater. (November 2021) - Wu, Zhen-Yu; Zhu, Wei-Ping; Liu, Yang; Zhou, Lu-Lu; Liu, Peng-Xi; Xu, Juan
Graphical abstract: Highlights: A novel biological-electrocatalytic system is developed to treat coking wastewater. 3DERs decompose NH4 + -N, NO3 – -N and COD by electrochemical redox reactions. BAFs convert NH4 + -N to NO3 – -N and remove partial COD. 3DBER mainly eliminates NO3 – -N by bio-electrochemical denitrification. The toxicity of coking wastewater is significantly reduced. Abstract: Coking wastewater is typically refractory, mainly due to its biological toxicity and complex composition. In this study, a novel integrated biological-electrocatalytic process consisting of two three-dimensional electrochemical reactors (3DERs), two biological aerated filters (BAFs), and a three-dimensional biofilm electrode reactor (3DBER) is developed for the advanced treatment of coking wastewater. 73.21% of chemical oxygen demand (COD), 38.02% of ammonium nitrogen (NH4 + -N) and 91.46% of nitrate nitrogen (NO3 – -N) are removed by 3DERs. BAFs mainly convert NH4 + -N to NO3 – -N through microbial nitrification. The 3DBER removes the residual NO3 – -N by bio-electrochemical denitrification. The integrated system can eliminate 74.72–83.27% of COD, 99.38–99.74% of NH4 + -N, and 69.64–99.83% of total nitrogen from coking wastewater during the continuous operation, as well as significantly reducing the toxicity of the wastewater. The superiorities of the integrated 3DERs/BAFs/3DBER system recommend the application of such biological-electrocatalytic technology in the treatment of highly toxic wastewater.